A Multi-level fuzzy logic scheme for modeling complex problems - Banda-Tapia, July Diana (2012)
In this paper, we propose to exte nd traditional Fuzzy Logic(FL) techniques by creating a second set of inference rules (and the corresponding inference mechanism) in order to effectively produce results exploitable by decision makers. We present a formal definition of a multi-level FL scheme and its application in the development of: i) a break-even inference machine and ii) a legal argumentation system. The proposed scheme is shown to be useful in modeling systems where intermediary fuzzy concepts come to play, and it could be applied in several problems analog to the ones presented in this study.